Analysis of Regional Original Income in Samarinda City - Bintang Samudera; Irwansyah Irwansyah; Diana Lestari (Universitas 45 Surabaya, 2025)
Regional development, as an integral part of national development, aims to optimize the utilization of human resources and other potential resources. One crucial factor in the success of regional development is the availability of adequate financial resources, which include general allocation funds, special allocation funds, central government balancing funds, and locally sourced revenues. This study analyzes the acceptance of Local Revenue (PAD) in Samarinda City by examining factors such as public expenditure, private investment, Gross Regional Domestic Product (GRDP), and per capita income. Using a multiple linear regression analysis method with time-series data from 2013 to 2023, the study finds that public expenditure has a positive but insignificant effect on PAD, while private investment, GRDP, and per capita income have a significant positive impact on PAD. The findings suggest that increasing local investment, economic growth, and per capita income can enhance the financial independence of Samarinda City. The study highlights the importance of policy formulation aimed at improving local revenue management and reducing dependency on central government transfers.